2007
DOI: 10.1021/jp076617l
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Oxidehydrogenation Activity of CeO2/Al2O3and V2O5/CeO2/Al2O3Catalysts

Abstract: Structural characterization and oxidative dehydrogenation activity of CeO 2 /Al 2 O 3 and V 2 O 5 /CeO 2 /Al 2 O 3 catalysts for ethylbenzene (EB) to styrene were investigated systematically. The CeO 2 /Al 2 O 3 catalyst was prepared by a deposition precipitation method, and a theoretical monolayer equivalent of 10 wt % V 2 O 5 was dispersed over its surface by a wet impregnation method to obtain the V 2 O 5 /CeO 2 /Al 2 O 3 catalyst. To understand thermal and textural stability, the synthesized catalysts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 59 publications
7
54
0
Order By: Relevance
“…The presence of consequently formed oxygen vacancies in the CeO2 lattice should result in a weak Raman peak at approx. 600 cm -1 [36]. This peak is not clearly observed ( …”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 86%
See 1 more Smart Citation
“…The presence of consequently formed oxygen vacancies in the CeO2 lattice should result in a weak Raman peak at approx. 600 cm -1 [36]. This peak is not clearly observed ( …”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 86%
“…645 cm -1 . This peak is a characteristic of the fluorite structure and is attributed to triply degenerate F2g mode [36]. The spectrum is altered upon the impregnation with Mn as the prominent peak is broadened, shifted towards a lower wavenumber and shows a well-recognized shoulder.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 97%
“…XRD patterns of VA show that four diffraction peaks at 2h values of 37.5 (311), With increase in the composition of ceria from 3 to 7 %, the intensity of diffraction peaks of ceria increases due to the increase in crystallinity of the catalysts. Incorporation of large size of Ce 3? ions in the vacant positions of small size alumina might be the reason for the presence of both alumina and ceria peaks in XRD spectrum [38]. The CeO 2 crystallite size calculated from Debye-Scherrer equation in all the ceria promoted catalysts comes to be *50 nm.…”
Section: Xrd Analysismentioning
confidence: 93%
“…The advantage of CeO X on V 2 O 5 /TiO 2 -ZrO 2 catalyst in maintaining steady EB conversion with high ST selectivity for a period of 10 h time on stream study was reported [46]. Another study highlighted the advantage of CeO X to V 2 O 5 /Al 2 O 3 catalyst in promoting the EB conversion in CO 2 at low temperatures [38]. Another study indicated that among different phases of CeO X , CeO 2 cubes are active for EB dehydrogenation [21].…”
Section: Spent Catalyst Studiesmentioning
confidence: 97%
“…Styrene is normally synthesized by two methods: mainly by an endothermic dehydrogenation of EB and as a coproduct of propylene oxide production [7][8][9][10]. The ODH of EB is a third possibility to produce styrene employing different oxidants, which has gained a great deal of attention recently [4][5][6][11][12][13][14][15]. The major advantage of the ODH process is that, unlike the endothermic dehydrogenation process, it can be operated at a lower temperature, as it is exothermic.…”
Section: Introductionmentioning
confidence: 99%